Gender Perspective: Self-Efficacy and Academic Stress of Middle School Students in Science Education - Fiandini, Meli; Lepir, Yenika Rambu; Rahmat, Adi; Hamdiyati, Yanti; Winarno, Nanang; Agustin, Mubiar (Universitas Pendidikan Indonesia (UPI), 2025)
This research aims to examine the influence of gender on self-efficacy and academic stress in middle school students in science subjects. A quantitative approach using a 40-item questionnaire consisting of measures of self-efficacy and academic stress, each containing 20 items, was administered. This research involved 51 students (consisting of 24 Males and 27 Females) in the ninth grade from private secondary schools in Bandung, Indonesia. Data analysis uses descriptive and inferential statistical techniques using Microsoft Excel and IBM SPSS software. The results showed significant gender differences in self-efficacy and academic stress. Male students show higher levels of self-efficacy than female students, while female students experience lower academic stress. These findings suggest potential interventions to increase self-efficacy and reduce academic stress in science courses, emphasizing gender-specific strategies.